Perlindungan Hukum Terhadap Pemegang Saham pada Proses Likuidasi Perseroan Terbatas ( Studi Kasus : Putusan Pengadilan Negeri Jakarta Pusat Nomor : 76/Pdt.P/2021/Pn Jkt.Pst ) - Bryan Yoppi Triatama; Moch. Hilal Rusydi Al Fiter; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
This article discusses the role of directors in the dissolution of a Limited Liability Company and the legal remedies taken by shareholders to protect their rights in the dissolution of a Limited Liability Company. The business activities of a Limited Liability Company do not always run in accordance with the objectives, sometimes the Company will face obstacles that cause the dissolution of the Limited Liability Company. With the dissolution of the Company, in this case the shareholders should get a legal protection both preventive and repressive. This research uses normative legal research with a statutory approach and a case approach through a decision study. The legal sources used are primary and secondary legal sources. Based on the results of the research, the Board of Directors of a Limited Liability Company in the process of dissolving the Company can act as a liquidator. Limited Liability Companies undergoing dissolution must pay attention to the rights and legal protection of shareholders.